(untitled) (diségno, 2021)
In the past decades, memory became one of the most popular thematics in architecture. Frequently associated with building restoration and historical design interventions, nowadays memory is acquiring new meanings which embrace its complexity by accepting the theoretical contributions coming from different fields and thus lending architecture an interdisciplinary aspect. This is particularly due to the breakthroughs achieved in both relative and quantum physics in the 20th century. With time, these discoveries introduced a new ontologic domain that questioned the scientific, artistic, and philosophical paradigms that are based on an outdated reading of reality. In the process of moving from discussing space to understanding spacetime, a designer discovers new dimensions, reconsiders his methodologies, and develops a unique vocabulary. In this scenario, to the intricate mechanisms that regulate the memory construction processes, Edmund Husserl and others added new representational techniques and computational workflows to suggest innovative alternatives to obsolete design methods.